STRUKTUR BAHASA AL-QUR’AN: MEMBANGUN ELEMEN STILISTIKA KEBAHASAAN DALAM AL-QUR’AN - Damhuri Damhuri (TAHKIM, 2017)
The meaning of a word in al-Qur'an is very important in the development of meaning theorization and its developer structure. It can review various styles and art for telling al-Qur'an from the words and sentence structure perspective as well as other peculiarities. Therefore, the existence of this article is a few review not only focuses on the sentence structure, but also the possibility of “transition” the meaning a vocabulary that in turn can influence the actions of meaning. In this discussion is possible the transition of meaning a word into another meaning influenced by the words and sentences structure. The presence of stylistics is viewing the beauty of al-Qur’an language, so it can be acceptable to all layers of community. Al-Qur’an touch (acceptable) the reason and sense, the harmony of series sentences of al-Qur’an and the wealth of editorial art. Key words: Structure, Stylistics, language, al-Qur'an